Comparing Results of a Study on Mathematics Instruction in English at Diploma College in Solapur District - Kazi Sultanabanu Sayyad Liyakat; Kazi Kutubuddin Sayyad Liyakat; Heena T Shaikh (Recent Trends in Mathematics, 2025)
Study programmes at the Diploma College in Solapur include mathematics courses, which are instructed in English. Comparing the educational outcomes in the Mathematics study course with the English language of instruction is the primary objective of the paper. We concentrated on the students' proficiency in solving specific linear algebra and mathematical analysis problems. The first-year students in the Diploma study programme in Diploma College, Solapur made up the research sample. In the academic years 2020–21 to 2022–23, partial tests, exam tests, and final grades in the mathematics exam provided empirical data. We discovered that students in the English-taught group outperform those in the Diploma College group on maths exams. The significance of variations in the points earned for each individual task in the examined study group has not been demonstrated by the results of hypothesis testing. While no single, universally applicable study compares the results of mathematics instruction in English at all diploma colleges, several research findings reveal consistent trends on the impact of English-medium instruction (EMI) on math performance. The comparison depends heavily on the students' language proficiency, the instructional methods used, and specific institutional contexts.
Keywords: English; exam grad; mathematics; maths test